(untitled) (Journal of the College of Education for Women, 2019)
Our scientists Arabs old efforts in achieving texts that led to the foundations of generalrules they have set for this work in accordance with the systematic context is based on thestudy, analysis and precision in dealing with this work, which became the basis for eachinvestigator to the present day, which was to them careful consideration manuscripts andwork to be closer to the image by its author, so produced their efforts in this area severalbooks provided the technical wizards of this science, which did not leave a gap in which onlygave her treatments and suggestions each and every one of the point made by and gave herwhat produced the expertise in this direction in accordance with the formulationsmethodology are balancing and application, any that Makedmoh such as advanced stage in theart of the investigation, who settled and clarified its features on their hands which they put theprimary application for this work, including the rules: the interview between copies, Repairerror and evaluate the melody and the treatment of miscarriage increases and settings, shape,making notes, writing and calligraphy and finally attention tool writing Pen..